Analysis of Multigene Mutations in Lung Adenocarcinoma in Zunyi. (29th May 2021) - Ma, Qingqing; Ma, Dengming; Lin, Mu; Gong, Yadong; Han, Xiaojing; Chen, Yunhua; Tang, Zhu; Liu, Mubo
Abstract : Objective . Driver gene mutation in lung adenocarcinoma patients in Zunyi and its relationship with clinical features were probed in this investigation. Methods . In total, with 244 patients with lung adenocarcinoma as study subjects, including 141 males and 103 females, amplification-refractory mutation system-polymerase chain reaction (ARMS-PCR) was utilized for detecting multigene mutations. Subsequently, the relationship between gene mutation and clinical characteristics was analyzed. Results . The total mutation rate of driver genes was 65.17%, including 48.36% EGFR, 6.15% KRAS, 5.74% ALK, 2.05% HER-2, 1.23% ROS1, 0.82% RET, 0.41% NRAS, and 0.41% BRAF. Among EGFR mutations, 47.46% were EGFR-19-deletion, 42.37% EGFR-21-L858R mutation, 4.24% EGFR-20-T790M mutation, 2.54% EGFR-21-L861Q mutation, 2.54% EGFR-20-insertion, and 0.85% EGFR-18-G719X mutation. Both female patients and nonsmoking patients with lung adenocarcinoma had a higher rate of EGFR mutation. Additionally, 15 patients with multiple mutations in EGFR, including 13 patients with 2 mutations in EGFR and 2 patients with 3 mutations in EGFR, were found. Conclusion . Among driver gene mutations in patients with lung adenocarcinoma in Zunyi, EGFR mutation has the highest incidence, followed by ALK fusion and KRAS mutation. Although both mutations and multisite mutations in the other driver genes account for a low proportion, they still have great clinical significance. Multigene mutation detection contributes to the rapid screening of patients with lung adenocarcinoma who respond to targeted therapy.